Chronic intermittent hypoxia-induced deficits in synaptic plasticity and neurocognitive functions: a role for brain-derived neurotrophic factor - Xie Hui; Yung Wing-ho (Acta Pharmacologica Sinica, 2016)
Obstructive sleep apnea (OSA) is well known for its metabolic as well as neurobehavioral consequences. Chronic intermittent hypoxia (IH) is a major component of OSA. In recent years, substantial advances have been made in elucidating the cellular and molecular mechanisms underlying the effect of chronic IH on neurocognitive functions, many of which are based on studies in animal models. A number of hypotheses have been put forward to explain chronic IH-induced neurological dysfunctions. Among these, the roles of oxidative stress and apoptosis-related neural injury are widely accepted. Here, focusing on results derived from animal studies, we highlight a possible role of reduced expression of brain-derived neurotrophic factor (BDNF) in causing impairment in long-term synaptic plasticity and neurocognitive functions during chronic IH. The possible relationship between BDNF and previous findings on this subject will be elucidated.